Studi Analisis Pengaruh Harmonisa Terhadap Rugi-Rugi Daya Pada Penyulang Menjangan - Wisnu Agung Bayuna, I Dewa Gede; Sukerayasa, I Wayan; Ariastina, Wayan Gede (Majalah Ilmiah Teknologi Elektro; Vol 16 No 1 (2017): (January - April) Majalah Ilmiah Teknologi Elektro, 2016)
Abstract— The content of harmonics on the electrical system if it exceeds the allowed limit will cause some problems, one of them is causing losses in power distribution networks. To determine the effect of harmonics on power losses in the feeder Menjangan, research conducted by the method of measuring the harmonics of each distribution substation in Menjangan feeders with the help of the software for the next simulation. From the results of the identification of patterns and spectrum curves wave harmonic content of the transformer feeder Menjangan, identical with the commercial load as the load of household and  electrical appliances are generally supplied from single-phase Switch Mode Power Supplies. From the measurement of harmonics, the highest content contained in distribution substation at the base are GR088 and GR079. The result of the calculation of the difference between the power loss in the condition without the content of harmonics and power loss in situations where the content of harmonics is 1.7991 kW.
Keywords: Kondisi tanpa Harmonisa; Kondisi dengan Harmonisa; Rugi Daya; Penyulang Menjangan